Pengaruh Semangat Kerja, Pemanfaatan Teknologi Informasi dan Kompetensi terhadap Kinerja Perangkat Desa di Kecamatan Tambak - Noviola Setia Rini; Nur `Khasanah (Jurnal Ilmiah Mahasiswa Manajemen, Bisnis dan Akuntansi (JIMMBA), 2023)
This study aims to determine the effect of morale, utilization of information technology, and competence on the performance of village officials in Tambak District. The population in this study were village officials in Tambak District, Banyumas Regency, with 121 village officials. The sample for this study consisted of 60 respondents drawn from all Tambak District village officials. The analytical tool used in this study is multiple linear regression analysis. The results showed that morale had no significant effect on the performance of village officials in Tambak District, with a significance value of 0.839 > 0.05 and the calculation results of 0.204Â  2.00030. With a significance value of 0.026 0.05 and calculation results obtained at a t value of -2.293 t = 2.00030, the use of information technology has a negative and significant effect on the performance of village officials in Tambak District. Competence has a significant effect on the performance of village wardens in Tambak District, with a significance value of 0.000Â  0.05 and the results of the calculations obtained being t = 6.836 > t = 2.00030.